PENERAPAN METODE BERMAIN DENGAN MERONCE UNTUK MENINGKATKAN MOTORIK HALUS DAN KOGNITIF ANAK PADA KELOMPOK B TK NEGERI 1 PAGAR ALAM - Disi Puslika; Nina Kurniah (DIADIK, 2021)
This study aims to describe the improvement of fine motor skills and cognitive through the application of the method of playing with meronce to group B children in TK Negeri 1 Pagaralam. The research design used was classroom action research and quasi-experimental. CAR is an action cycle consisting of 3 cycles from the planning, implementation, observation and reflection stages. The PTK subjects are children of group B1 even semester of the 2020/2021 school year. The sample of the experimental group was group B2 and control group B3 TK Negeri 1 Pagaralam. The research instrument used observation sheets, tests and work results. The research data were analyzed using descriptive statistics, mean, percentage, and t-test. The results of the study increased significantly in each action cycle seen from the increase in children's fine motor skills and cognitive abilities seen from the classical completeness of the first cycle was only 28% of the MB criteria, increased in cycle II by 57% of the BSH criteria and the third cycle reached 100% of the BSB criteria using the method. playing with meronce in group B of TK Negeri 1 Pagaralam